Reactor nozzle inspection based on the laser-guided mobile robot. (8th January 2018) - Kim, Jae-Hee
Most inspection and repair works are performed with robots in a nuclear power plant, as a human operator cannot access the facility due to radiation. In order to ensure the integrity of the reactor vessel, the reactor nozzle welds should be inspected periodically. The inspections have been performed using a conventional inspection machine with a large sturdy column; however, these machines are so large and heavy that their handling and maintenance requires much effort. In order to resolve these kinds of problems, the authors have developed a mobile robotic manipulator, which is very small and light and easy to handle. The underwater mobile robot with magnetic wheels is guided by a laser beam for its accurate positioning. Even though the inspection system is light and simple, its accurate positioning for reactor nozzle weld inspection is much more difficult and complex. This article explains how to position our laser-guided mobile robot manipulator at the reactor vessel wall and determines the pan and tilt angle of the laser pan-tilt device to guide the robot along a specified path around the nozzle. We derive the path planning of the mobile robotic manipulator when inspecting nozzle welds on the upper shell of the vessel, and we experimented the whole robotic system to identify position accuracy of the robot movements through the inspection scanning of reactor nozzle.